AN EXAMPLE OF WHAT MACEDONIAN POPULATION KNOWS ABOUT FOOD ALLERGIES AND FOOD INTOLERANCE - Uzunoska Zora, Kalevska Tatajana, Stamatovska Viktorija, Belichovska Katerina, Belichovska Daniela, Damjanovski Dragan (Consulting and Training Center KEY, Mito Hadzi Vasilav Jasmin, Skopje, Macedonia, 2017)
A food allergy is a widespread disease, an exaggerated immune system response mostly to a food proteins, mediated by Ig E antibodies, followed by a certain clinical picture ranging from a mild to life threatening symptoms. Eight foods cause 90% of allergies: milk, egg, peanuts, tree nuts, fish, shell fish, wheat and soy. However, any food can cause an allergic reaction. Food intolerance is an adverse reaction to food that does not involve the immune system. A pilot study to detect what Macedonians know about food allergies and intolerance. A Questionnaire composed of 12 questions was put on Faculty of Technology and Technical Sciences website and answers of 130 persons from different regions of Macedonia were collected. The participants were categorized by sex and age (from 18 to 29; 30 - 39; and over 40). The results obtained by arithmetical mean and expressed in percentage were analyzed. 63% of them know what kind of food can often cause an allergy, 60% know about the symptoms, 73% know that allergy can be fatal, 66% does not know how to prevent the symptoms, 69% think that food allergy does not disappear throughout the life, 87% do read the declaration of the food product they are buying, 79% think that the food products are not properly labeled for allergic substances, 53% do not know the intolerance symptoms and 70% do not know how to protect themselves from food intolerance. Macedonians are quite well informed about food allergies, their symptoms and fatal outcome, but are less informed about its prevention as well as about food intolerance. There should be more sufficient labeling of all allergic substances on the food products in Macedonia. A wider population should be included in the survey to confirm these findings.
Keywords: Food, Allergy, Allergens, Intolerance.